2014
DOI: 10.1007/s10616-014-9761-9
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive pharmacological differences between liver cancer cell lines HepG2 and Hep3B

Abstract: As cellular models for in vitro liver cancer and toxicity studies, HepG2 and Hep3B are the two most frequently used liver cancer cell lines. Because of their similarities they are often treated as the same in experimental studies. However, there are many differences that have been largely over-sighted or ignored between them. In this review, we summarize the differences between HepG2 and Hep3B cell lines that can be found in the literature based on PubMed search. We particularly focus on the differential gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 91 publications
1
94
0
7
Order By: Relevance
“…We previously demonstrated that ER calcium store depletion is a central mediator of post-burn hepatic ER stress [10]. To model this in vitro we depleted ER calcium stores with the SERCA pump inhibitor thapsigargin (TG) in HepG2 hepatoma cells, a well-characterized polarized human hepatocyte cell line model [32, 33]. We hypothesized that ER stress may lead to the release of aggregated proteins and/or extracellular vesicles into the media which could function as DAMPs.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that ER calcium store depletion is a central mediator of post-burn hepatic ER stress [10]. To model this in vitro we depleted ER calcium stores with the SERCA pump inhibitor thapsigargin (TG) in HepG2 hepatoma cells, a well-characterized polarized human hepatocyte cell line model [32, 33]. We hypothesized that ER stress may lead to the release of aggregated proteins and/or extracellular vesicles into the media which could function as DAMPs.…”
Section: Resultsmentioning
confidence: 99%
“…All the seven compounds elicited a concentration‐dependent cytotoxic activity against both HepG2 and Hep3b cell lines without marked difference between the two cell lines. The fact that no significant difference was observed in the cytotoxic effect against HepG2 and Hep3b despite the distinct pharmacological properties of the two cell lines , suggested a cell line‐independent mechanism of action of the compounds. Indeed, it is accepted that the cytotoxicity of ent ‐kaurane diterpenoids results from the formation of reactive oxygen species (ROS) through Michael reaction with regulatory thiol‐containing enzymes or coenzymes , likely to be shared by the two HepG2 and Hep3b cell lines and others.…”
Section: Discussionmentioning
confidence: 96%
“…To explore the biochemical and pharmacological properties of solasonine, we used the well‐characterized human HepG2 and Hep3b cell lines described to represent cellular reference models for in vitro pharmacological studies and proven well adapted for the study of new molecules active on HCC . In addition, of the numerous cell lines used to study hepatocellular carcinoma, both the HepG2 and Hpe3b cell lines are among those which correlate the best to hepatocellular carcinoma tumors, HepG2 being the one displaying the highest correlation .…”
Section: Discussionmentioning
confidence: 99%